Advances in computational thinking and robotics in education - García-Peñalvo, Francisco José (2021)
After the computational thinking sessions in the previous 2016-2019 editions of TEEM Conference, the fifth edition of this track has been organized in the current 2020 edition. Computational thinking is still a very significant topic, especially, but not only, in pre-university education. In this edition, the robotic has a special role in the track, with a strength relationship with the STEM and STEAM education of children at the pre-university levels, seeding the future of our society.